KEEFEKTIFAN STRATEGI MENULIS TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN MENGARANG NARASI - Yunismar Yunismar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the low learning outcomes of students' narrative writing skills at SDN 003 Tasik Juang. This research was conducted in class IV with a total of 25 students. The purpose of this study is to improve students' narrative writing skills by implementing guided writing strategies. This research is a class action research consisting of two cycles with stages of planning, action, observation and reflection. The results showed in learning 1 the number of students who completed as many as 19 people with a percentage of 76% and as many as 6 people who did not complete with a percentage of 24%. In learning 2 the number of students who completed as many as 21 people with a percentage of 84% and as many as 4 people who did not complete with a percentage of 16%. In learning 3 the number of students who completed as many as 22 people with a percentage of 88% and as many as 3 people who did not complete with a percentage of 12%. In the last study, the number of students who completed as many as 23 people with a percentage of 92% and as many as 2 people who did not complete with a percentage of 8%. Based on the results of this study it can be concluded that the implementation of the guided writing strategy has proven to be effective in improving the learning outcomes of narrative writing skills of the fourth grade students of SDN 003 Tasik Juang